Randomized controlled single‐blinded clinical trial of functional voice outcome after vascular targeting KTP laser microsurgery of early laryngeal cancer. Issue 4 (31st January 2019) - Strieth, Sebastian; Ernst, Benjamin P.; Both, Ina; Hirth, Daniel; Pfisterer, Lara N.; Künzel, Julian; Eder, Katharina
Abstract: Background: Local control rate (LCR) of early glottic cancer is high after radiation therapy or transoral laser microsurgery (TLM). The aim of this study was to investigate functional voice outcome after TLM using a microvessel‐ablative potassium‐titanyl‐phosphate (KTP) laser in comparison with a gold standard cutting CO2 laser. Methods: The primary end point of this prospective, randomized, single‐blinded, clinical phase II study with control group was voice outcome during a follow‐up of 6 months assayed by Voice Handicap Index (VHI‐30)‐questionnaires in patients with unilateral high‐grade dysplasia, carcinoma in situ or early glottic cancer undergoing TLM‐KTP (n = 8) or TLM‐CO2 (n = 12). The secondary end point was LCR. Results: Starting from the 9‐week‐follow‐up visit, TLM‐KTP yielded significantly reduced VHI scores compared to TLM‐CO2 . No relapse occurred after TLM‐KTP in contrast to one recurrence after TLM‐CO2 within 6 months. Conclusion: Multicenter phase II or III studies on voice outcome or local control rate after TLM‐KTP in early glottic cancer are warranted enrolling larger patient cohorts.